Application of fiscal federalism theory to the constitutional organisation of Czechoslovakia after establishment of Federation at different stages of historical context - Baláži, Peter
Fiškálny federalizmus v rokoch 1968-1970 a v rokoch 1971-1988. Porovnanie príjmov a výdavkov federácie a národných rozpočtov.